Characterization of Te nanoparticles synthesized by plasma processing. (October 2020) - Iesari, Fabio; Hatada, Keisuke; Patel, Jigar; Balasubramanian, Chidambara; Miyanaga, Takafumi; Ikemoto, Hiroyuki
Abstract: The local structure of Tellurium nanoparticles synthesized by arc plasma were studied by X-ray absorption spectroscopy. Nanoparticles were characterized by using different techniques to reveal particles size, morphology and composition. Te K-edge EXAFS spectra reveal a structure similar to trigonal Te, where both the inter-chain and intra-chain bonds, typical of Te crystal structure, are present. Evolution of the Debye-Waller factor with temperature reveals an increased static disorder in the nanoparticles respect to the trigonal material. Highlights: Size of Te nanoparticles created by plasma processing is around 100 nm. Inter-chain interactions are preserved. Increase of static disorder respect to crystal Te.